A simple and inexpensive way to document simple husbandry in animal care facilities using QR code scanning. (December 2017) - Green, Tyler; Smith, Terry; Hodges, Richard; Fry, W Mark
Record keeping within research animal care facilities is a key part of the guidelines set forth by national regulatory bodies and mandated by federal laws. Research facilities must maintain records of animal health issues, procedures and usage. Facilities are also required to maintain records regarding regular husbandry such as general animal checks, feeding and watering. The level of record keeping has the potential to generate excessive amounts of paper which must be retained in a fashion as to be accessible. In addition it is preferable not to retain within administrative areas any paper records which may have been in contact with animal rooms. Here, we present a flexible, simple and inexpensive process for the generation and storage of electronic animal husbandry records using smartphone technology over a WiFi or cellular network.